Connecting Idioms and Metaphors: Where Cognitive Linguistics Meets Cognitive Stylistics - Kovaliuk, Yurii (THE DEPARTMENT OF ENGLISH LANGUAGE AND LITERATURE, UNIVERSITY OF TIMIŞOARA, 2024)
The article discusses important issues in the conceptual analysis of English idioms based on a multilayered online processing view of metaphor and the cognitive stylistic analysis of idioms, in an attempt to reconcile the two lines of research. The study focuses on idioms grouped under the semantic category of argument and conflict. First, the idioms are analysed from the perspective of the multilayered online processing view of metaphor. Second, the relevant cognitive stylistic features of idioms are described. The hypothesis that the multilevel view of metaphor can help establish certain conceptual regularities in semantically related idioms is investigated.
Keywords: cognitive stylistics, conceptual metaphor, extended idiomatic metaphor, idiom, linguistic metaphor, multilevel view of metaphor